PERENCANAAN KARIR SEBAGAI BENTUK INVESTASI PENDIDIKAN SISWA SMK (STUDI KASUS DI SMK NEGERI 1 BATANG) - Arina Hidayati (Jurnal Pendidikan Ilmu Sosial, 2015)
The Vocational School was established by the goal to prepare the learners for entering the job field. However, the fact at the field showed that The Vocational School contributed the highest jobless in Indonesia. This fact happened because the competence that was owned by the graduators of Vocational School have not fulfilled competence standard that is needed by the job world and industry. The graduators’ competence of vocational school can be increased by giving training and advanced education after graduated from school. The advanced education is not always in the university level, it means that the advanced education can be formed education to strength the field that is learned by the students during at school that is in line with the job world. However, the importance of education investment have not owned by the society. The society more oriented the graduators of Vocational School for getting job straightly without competence measurement that is owned by them. Therefore, the workers’ career of the Vocational School not as good as the other workers who have recognized for increasing their competence through education. The beginning of recognizing of education investment can be done by activating the career planning program. This Program can give direction to the students of Vocational School in order able to measure their own competence. So that, when those students chose the job can be in line with their competence.